Implikasi Kinerja Bisnis dari Penerapan Manajemen Rantai Pasokan Hijau (Perspektif Pemasukan) - Bekti Wijoyo Kusumo (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This study explores the implications of implementing Green Supply Chain Management (GSCM) on business performance, with a focus on the income or inbound perspective. GSCM is an approach that aims to reduce the environmental impact of supply chain activities while improving operational efficiency and sustainability. Through a review of various GSCM practices in the revenue process, this study identified positive impacts on business performance, including increased efficiency, reduced costs, improved corporate reputation, and customer engagement and satisfaction. This analysis provides important insights for organizations seeking to adopt GSCM practices in an effort to improve their business performance and sustainability. Keywords: Green Supply Chain Management, Business Performance